N-Acetyl-2-hydroxy-N′-[methoxy(1-methylindol-2-yl)methyl]benzohydrazide - Yehye, Wagee A. (International Union of Crystallography, 2008)
In the crystal structure of the title Schiff-base, C(20)H(21)N(3)O(4), the amino group forms an N—H⋯O hydrogen bond to the acetyl group of an adjacent molecule, forming a zigzag chain. The 2-hydroxy group is internally hydrogen bonded to the amido group though an O—H⋯O hydrogen bond.